The study of motives and the Issues of Mixed-Marriages in Saudi Arabia: An Inductive Analytical Approach in Literature Review - Alduraywish, Munirah Abdallah Ali (Journal of Humanities & Social Sciences, 2023)
The current study is a literature review utilizing an inductive analytical approach of previous published local studies that dealt with the marriage of Saudi citizens to non-Saudis, to identify the issues that face of mixed families in Saudi Arabia. The two main goals of the current study are: (1) Identifying the motives behind mixed marriages, and (2) highlighting the issues associated with them in Saudi Arabia. The result of current study led to the following findings: First, mixed families face several issues related to citizenship and nationality. Second, these families also face social problems such as: negative perception of society, its attitudes toward mixed marriage, sociocultural heterogamy, in addition to disagreement and conflict in marriage, and religious heterogamy، as well as the issues of linguistic communication; moreover, social problems brought on by divorce. Third: people from mixed-race families may experience racial prejudice at workplaces, schools, and on social media. Fourth: mixed families may also encounter issues with government assistance, and financial stability. Fifth: there are some moral and security issues that arise from mixed marriages. Sixth: researchers who examine the issues of mixed marriages are struggling with the lack and inconsistency of data about mixed marriages in Saudi Arabia. The study recommends the following (1) improving the laws and regulations that pertain to mixed families (2) promoting public awareness public of the consequences of mixed marriage, (3) suggesting further studies of mixed families challenges in the academic and scientific fields.
Keywords: Inductive; analytical approach; mixed-marriages; citizenship; mixed marriages motives; social issues